Media Role of Learning on the Improvement of Learning Outcomes in Concept Distribution in Math Class IV - Nurhani Mahmud (Peneliti.net, 2020)
This study aims to determine the role of instructional media, especially picture media on the improvement of mathematics learning outcomes in the concept of division in class IV Daeo Inpres Elementary School. This type of research is a Classroom Action Research (CAR) with research subjects of 30 students consisting of 12 women and 18 men. This action research was carried out with two cycles consisting of stages: planning, implementation, observation and reflection. Data collection techniques through observation and tests and data were analyzed in quantitative descriptive form. The results of this study indicate that the application of learning media can increase the activities of students and teachers in the teaching and learning process. Student activity from Cycle I an average score of 35% increased in cycle II to an average score of 95%. Likewise, teacher activity in cycle I had an average score of 40% and in cycle II teacher activity had increased with an average score of 92.50%. Likewise, student learning outcomes have increased from the first cycle to an average score of 51.38 and in the second cycle reached 83.33% or 25 students who completed 30 students. Classically the learning outcomes have reached the K